# Cosx=cosy

## Simple and best practice solution for Cosx=cosy equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Cosx=cosy equation:

Simplifying
Cosx = cosy
Solving
osxC = cosy
Solving for variable 'o'.
Move all terms containing o to the left, all other terms to the right.
Add '-1cosy' to each side of the equation.
-1cosy + osxC = cosy + -1cosy
Combine like terms: cosy + -1cosy = 0
-1cosy + osxC = 0
Factor out the Greatest Common Factor (GCF), 'os'.
os(-1cy + xC) = 0
Subproblem 1Set the factor 'os' equal to zero and attempt to solve:
Simplifying
os = 0
Solving
os = 0
Move all terms containing o to the left, all other terms to the right.
Simplifying
os = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1cy + xC)' equal to zero and attempt to solve:
Simplifying
-1cy + xC = 0
Solving
-1cy + xC = 0
Move all terms containing o to the left, all other terms to the right.
Add 'cy' to each side of the equation.
-1cy + cy + xC = 0 + cy
Combine like terms: -1cy + cy = 0
0 + xC = 0 + cy
xC = 0 + cy
Remove the zero:
xC = cy
Add '-1xC' to each side of the equation.
xC + -1xC = cy + -1xC
Combine like terms: xC + -1xC = 0
0 = cy + -1xC
Simplifying
0 = cy + -1xC
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`